The Virtual Course of Persian and Complementary Medicine of Smart University of Medical Sciences from the Students' Point of View: An Online Survey Study - Amin Habibi; Taiebe Shokri; Babak Sabet; Hossein Rezaeizadeh; Hamed Khani; Fatemeh Nasouri (Tehran University of Medical Sciences, 2024)
Persian medicine is an ancient medical school that prioritizes preserving health over treatment. It is a holistic approach that considers genetics, lifestyle, and other factors to find the root cause of a disease. This study investigated the virtual course of Persian and complementary medicine from the perspective of students. We conducted a cross-sectional study. A standard questionnaire was used to collect data from 750 participants. The tool's validity was confirmed based on its content validity, and Cronbach's alpha coefficient was used to estimate the internal consistency of this questionnaire. The questionnaire measured the effectiveness of the virtual education system in various dimensions, and the participants completed it electronically at the end of the course. SPSS 26.0 was used to analyze the collected data. The study used frequency, percentage, and mean to describe data and a desirability score was calculated for each question to evaluate course quality from participants' perspective. The results of the one-sample t-test indicate that the sample mean (57.111) is higher than the population mean (90) (p < 0.01). Based on the independent samples t-test, the mean attitude score of female students towards course is higher than that of male students (p > 0.05). The ANOVA analysis results regarding the mean attitude scores of students towards the course based on their field of study show that the mean attitude scores vary across different fields of study (p < 0.05). The result of present study emphasizes the importance of developing education in Persian medicine in universities to meet the clinical needs of the community and improve health and well-being. This can also promote the status of Persian medicine globally.